PERAN BAHASA INDONESIA DALAM PEMBELAJARAN FISIKA: EKSPLORASI STRATEGI DAN DAMPAKNYA TERHADAP PEMAHAMAN KONSEP - Evita Flora Pinem; Tasya Irene Pandiangan; Latipa Anum Lubis; Fatricya Handayani; Nurul Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Apart from being used as a communication tool, Indonesian is also used to increase the competence of human resources. Quality human resources can be achieved by optimizing a series of physics learning processes in achieving learning goals at school. To achieve the expected physics learning objectives, language skills are needed, skills in using language in accordance with the provisions aimed at making it easier to understand science. Language accuracy is one of the skills in using language. If the use of language in the physics learning process in the classroom is inappropriate, it will give rise to students' misperceptions in absorbing the physics concepts explained by the supervisor. If this cannot be avoided, it will give rise to misconceptions in knowledge transfer activities. In this article, to find out how important the role of Indonesian is in learning physics, a quantitative research was carried out using the questionnaire method, where this questionnaire contained three questions and was given to thirty respondents from various levels of education. Based on the results of this research, it is proven that the role of Indonesian is very important in the physics learning process. Remembering that the learning process is related to the interaction between supervisors and students through language.